Efficacy and safety of insulin-GLP-1 receptor agonists combination in type 2 diabetes mellitus: a systematic review. (1st December 2016) - Cimmaruta, D; Maiorino, MI; Scavone, C; Sportiello, L; Rossi, F; Giugliano, D; Esposito, K; Capuano, A
ABSTRACT: Introduction: Attaining optimal glycemic targets in patients with type 2 diabetes is often hard and compromised by the shortcomings of the several treatments. Areas covered: When glycemic levels are not adequately controlled, an association of GLP-1 receptor agonists and insulin therapy can be adopted. In order to assess the benefit/risk profile of this combination therapy, a literature search of randomized clinical trials was performed.Eighteen trials matched the inclusion criteria. In 10 studies, GLP-1 receptor agonists were added on to an existing regimen, whereas insulin added to an existing GLP-1 receptor agonists regimen occurred in 2 studies. Six studies compared GLP-1 receptor agonists with short acting insulin as a treatment strategy to intensify basal insulin therapy. Expert opinion: Clinical trials herein reviewed demonstrated the safety and the efficacy of combining GLP-1 receptor agonists with basal insulin, with most studies showing equal or slightly superior efficacy, as compared with the addition of prandial insulin, associated with weight loss and less hypoglycemia.